2015
DOI: 10.1111/dme.12710
|View full text |Cite
|
Sign up to set email alerts
|

Bioimpedance phase angle indicates catabolism in Type 2 diabetes

Abstract: The phase angle at 100 kHz is a promising measurement for assessing catabolic state in people with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 28 publications
2
72
0
3
Order By: Relevance
“…Different from the other parameters used to assess body composition measured by BIA, the PhA is considered to be valid also when the hydration status varies, as in obesity and chronic inflammation [ 19 , 20 , 36 ]. Small PhA was reported in patients with cancer [ 20 ], diabetes [ 21 ], and obesity [ 22 ], possibly because of a reduction in the mass of metabolically active cells [ 37 ]. In addition, the adjunctive effect on cell damage of the inflammatory status, commonly accompanying these conditions, should be considered [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different from the other parameters used to assess body composition measured by BIA, the PhA is considered to be valid also when the hydration status varies, as in obesity and chronic inflammation [ 19 , 20 , 36 ]. Small PhA was reported in patients with cancer [ 20 ], diabetes [ 21 ], and obesity [ 22 ], possibly because of a reduction in the mass of metabolically active cells [ 37 ]. In addition, the adjunctive effect on cell damage of the inflammatory status, commonly accompanying these conditions, should be considered [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In disease conditions, including MetS, PhA values are frequently lower than normal since either disease-specific parameters and disease-related inflammatory status may impair PhA [ 19 ]. In this regards, the use of the PhA has been recommended as a prognostic marker of mortality in various chronic diseases [ 20 ], including cancer, and is associated with risk of morbidity in diabetes [ 21 ] and obesity [ 22 ]. As long as we know, data on the risk of morbidity in psoriatic patients and the association between PhA and MetS the clinical setting of the chronic, systemic inflammatory status mutual to both conditions are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 In all these studies, PA is concluded to be an early indicator of malnutrition and correlates well with other standard methods of nutrition evaluation including underwater weighing, 22 isotope dilution, and total body potassium. 23 It is postulated that PA value is readily affected by the subtle alterations of integrity of cell membrane and may reflect even the earliest changes of the nutrition patterns. 24 Therefore, our study adds to the pool of evidence directed to the further research and clinical implementation of malnutrition diagnostics using BIA in HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…PhA is used as an indicator of cellular health in relation to imbalance of cellular water and integrity of the cell membrane [8]. However, the PhA value can be negatively influenced by several clinical diseases, such as malnutrition [9], diabetes [10], human immunodeficiency virus infection (HIV infection) [11], and some types of cancer [12,13]. Healthy individuals show higher values of PhA (higher than 5º), indicating better cellular health and cell membrane integrity compared to malnourished patients [9].…”
Section: Introductionmentioning
confidence: 99%